The results of endoscopic and surgical methods of hemostasis in persons of elderly and senile age with acute gastrointestinal bleeding caused by an ulcer - Zavhorodnii, S. M.; Kapshytar, O. V.; Kotenko, O. I.; Kapshytar, O. O.; Danyliuk, M. B. (Zaporozhye Medical Journal, 2022)
The aim of the study. To define the number of acute gastrointestinal bleeding cases due to ulcer and to analyze the results of endoscopic and surgical methods of hemostasis in elderly and senile patients. Materials and methods. In total, 463 patients with acute gastrointestinal bleeding (AGIB) due to ulcer were treated between 2019 and 2020. There were 323 persons over 60 years of age (69.8 %). A risk for bleeding was identify according to the Forrest Classification (2006). Local hemostasis was performed in 68 (21.1 %) patients over 60 years of age. Results. Group A (n = 32; 47.1 %) was represented by patients who underwent endoscopic hemostasis by diathermocoagulation, and local hemostasis was achieved. The indication was the bleeding activity: FIa in 4 (12.5 %) patients, FIb – in 14 (43.8 %), FIIa – in 1 (3.1 %), FIIb – in 6 (18.8 %) and FIIc – in 7 (21.9 %). Successful hemostasis was achieved in 24 (75 %) patients, and they were discharged. Recurrent massive AGIB was observed in 8 (25 %) patients for 2–6 days. We have identified the causes of recurrent bleeding: giant ulcers on the posterior wall of the duodenal bulb, lesser curvature and gastric cardia, active bleeding at the time of hemostasis, prehospital anticoagulants, decompensated concomitant pathology. Emergency laparotomy with variants of surgical hemostasis was performed in 6 (75 %) patients. After the operation, 5 (83.3 %) patients died (hemorrhagic shock – 2, multiple organ failure – 2, pulmonary embolism – 1). Repeated endoscopic hemostasis was performed for 2 (25 %) patients with a fatal outcome in both cases. Group B (n = 36; 52.9 %) was represented by patients with F1a stigma who failed to perform endoscopic hemostasis and underwent surgical hemostasis. 16 (44.4 %) patients died (hemorrhagic shock – 8, multiple organ failure – 5, polymorbid state – 2, pulmonary embolism – 1). Conclusions. Among patients with AGIB due to ulcer, persons over 60 years old accounted for 69.8 %, among whom local hemostasis was performed in 21.1 % with the prevalence of surgical hemostasis over endoscopic one, 52.9 % and 47.1 %, respectively. Surgical hemostasis options were traumatic, more reliable, but resulted in a high mortality rate – 44.4 %. Endoscopic hemostasis was low-traumatic, successful in 75 % of patients, non-effective in the form of massive rebleeding episodes – in 25 %, followed by surgical hemostasis, that led to the high mortality rate – 83.3 %.